2011
DOI: 10.1007/s11605-010-1370-0
|View full text |Cite
|
Sign up to set email alerts
|

Suture-Free Anastomosis of the Colon Experimental Comparison of Two Cyanoacrylate Adhesives

Abstract: The tissue adhesive Glubran 2 appears to be (under experimental conditions) a promising synthetic adhesive for colonic anastomosis construction; conversely, the tissue adhesive Dermabond was unsuitable for suture-free anastomosis construction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 28 publications
2
24
0
2
Order By: Relevance
“…Besides CA dosage, inversion of a gastrointestinal anastomosis has been considered as a key factor in anastomotic healing [22], and was also essential to the reinforcement technique discussed in this study. Some previous studies reported a leakage rate of 34% in everting CA-sealed anastomoses [23,24], while in another study, no leakage and good wound healing were found when a modified circular stapler was used to create inverted anastomoses sealed with CA [13]. These aspects and other technical details of CA's application should also be taken into consideration for AL studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides CA dosage, inversion of a gastrointestinal anastomosis has been considered as a key factor in anastomotic healing [22], and was also essential to the reinforcement technique discussed in this study. Some previous studies reported a leakage rate of 34% in everting CA-sealed anastomoses [23,24], while in another study, no leakage and good wound healing were found when a modified circular stapler was used to create inverted anastomoses sealed with CA [13]. These aspects and other technical details of CA's application should also be taken into consideration for AL studies.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown to provide strong mechanical attachment and polymerize quickly within 30-60 s after application [11]. Clinical practice showed promising results on the use of CA as a sealant after primary anastomosis in pancreaticoduodenectomy [12]; experimental studies also used CA to create sutureless colorectal anastomoses [13]. These results suggested that CA seemed to be a promising alternative to supportive sutures in low colorectal anastomosis.…”
Section: Introductionmentioning
confidence: 99%
“…Nine studies regarding NBCA were included (Table II). Among these, three studies focused on the sutureless anastomosis, three studies looked into NBCA sealant, and the other three tested both applications . In the NBCA studies, all four large animal studies had positive results, whereas of the other five rat studies only one had positive outcomes …”
Section: Resultsmentioning
confidence: 99%
“…Only NBCA showed good wound healing without stenosis after 4 or 12 weeks . Another comparison between NBCA (Glubran 2) and OCA (Dermabond) was performed in a porcine model . The CA sutureless anastomoses were constructed in the colorectum with a modified stapling device in which all the staples were taken out in advance.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation